Evaluasi Program Pembelajaran IPA Kelas VII di SMP Negeri 21 Jakarta - Nur’ Amaliah Mardiawati; Musringudin Musringudin (Publikasi Indonesia, 2022)
The purpose of this study was to determine the effectiveness of the science learning process by using the evaluation of the CIPP Contexts, Input, Process, Product) model at SMP Negeri 21 Jakarta. Determination of the effectiveness of a learning process is seen from the level of achievement of the learning objectives that have been determined at the beginning of learning. This research was qualitative research that uses the CIPP model by evaluating each component of the context, input, process and product to achieve an effective learning process. Sources of research data were science teachers, curriculum representatives, and school principals at SMP Negeri 21 Jakarta. Primary data collection using observation instruments while secondary data obtained through documentation and interviews. The data obtained from observations, documentation and interviews were then analysed descriptively and qualitatively. The results of the study indicate that the implementation of learning which includes the requirements for implementing learning and learning activities is quite effective.